Epilepsy with Occipital Calcifications - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Four patients, aged 13-22 yrs, with focal epilepsy, and bilateral occipital corticosubcortical calcifications without facial cutaneous angioma were followed at the Neurological Institute, University of Bologna Medical School, Via Ugo Foscolo, Bologna, Italy, and were found to develop a severe encephalopathy with progressive mental impairment.